Early adoption of screening and the changing pattern of cervical cancer in UK military women: evidence from the Scottish Veterans Health Study. Issue 5 (18th December 2015) - Bergman, Beverly P; Mackay, DF; Pell, JP
Abstract : Objective: To examine the risk of cervical cancer in a large national cohort of military veteran women followed up for up to 30 years. Methods: Retrospective cohort study of 5235 veteran women born between 1945 and 1985, and 20 703 women with no record of service matched for age and area of residence, using Cox proportional hazard models to compare the overall risk of cervical cancer and by year of birth. Results: During the follow-up period 1981–2012, there were 18 (0.34%) cases of cervical cancer in the veteran women compared with 81 (0.39%) in the non-veterans. The difference was not statistically significant overall (adjusted HR 0.95, 95% CI 0.57 to 1.59). When analysed by the year of birth, veteran women born in 1958 and earlier had a non-significantly higher risk than non-veterans (adjusted HR 1.24, 95% CI 0.68 to 2.26), while veteran women born after 1958 had a non-significant reduction in risk (adjusted HR 0.51, 95% CI 0.18 to 1.44). Conclusions: Women born after 1958 who have served in the Armed Forces are at reduced risk of cervical cancer compared with women who have never served, and compared with older veteran women. Small numbers of cases precluded statistical significance. The change in risk pattern in veteran women coincided with the introduction of cervical screening in the Armed Forces, which predated the UK national programme, and provides evidence for the long-term effectiveness of the Armed Forces' sexual health strategy. The impact of recent changes in the screening age, and of human papillomavirus immunisation, should be monitored in the future.